2019 Mark Coventry Award: A multicentre randomized clinical trial of tranexamic acid in revision total knee arthroplasty: does the dosing regimen matter?. (July 2019) - Fillingham, Y. A.; Darrith, B.; Calkins, T. E.; Abdel, M. P.; Malkani, A. L.; Schwarzkopf, R.; Padgett, D. E.; Culvern, C.; Sershon, R. A.; Bini, S.; Della Valle, C. J.; ,
Abstract : Aims: Tranexamic acid (TXA) is proven to reduce blood loss following total knee arthroplasty (TKA), but there are limited data on the impact of similar dosing regimens in revision TKA. The purpose of this multicentre randomized clinical trial was to determine the optimal regimen to maximize the blood-sparing properties of TXA in revision TKA. Patients and Methods: From six-centres, 233 revision TKAs were randomized to one of four regimens: 1 g of intravenous (IV) TXA given prior to the skin incision, a double-dose regimen of 1 g IV TXA given both prior to skin incision and at time of wound closure, a combination of 1 g IV TXA given prior to skin incision and 1 g of intraoperative topical TXA, or three doses of 1950 mg oral TXA given two hours preoperatively, six hours postoperatively, and on the morning of postoperative day one. Randomization was performed based on the type of revision procedure to ensure equivalent distribution among groups. Power analysis determined that 40 patients per group were necessary to identify a 1 g/dl difference in the reduction of haemoglobin postoperatively between groups with an alpha of 0.05 and power of 0.80. Per-protocol analysis involved regression analysis and two one-sided t -tests for equivalence. Results: In total, one patient withdrew, five did not undergo surgery, 16 were screening failures, and 25 did not receive the assigned treatment, leaving 186 patients for analysis. There was no significant difference in haemoglobin reduction among treatments (2.8 g/dl for single-dose IV TXA, 2.6 g/dl for double-dose IV TXA, 2.6 g/dl for combined IV/topical TXA, 2.9 g/dl for oral TXA; p = 0.38). Similarly, calculated blood loss (p = 0.65) and transfusion rates (p = 0.95) were not significantly different between groups. Equivalence testing assuming a 1 g/dl difference in haemoglobin change as clinically relevant showed that all possible pairings were statistically equivalent. Conclusion: Despite the higher risk of blood loss in revision TKA, all TXA regimens tested had equivalent blood-sparing properties. Surgeons should consider using the lowest effective dose and least costly TXA regimen in revision TKA. Cite this article: Bone Joint J 2019;101-B(Supple 7):10–16